Peningkatan Kesejahteraan Keluarga Melalui Pelatihan Wirausaha Produk Camilan Sehat Stik Seafood bagi Ibu Rumah Tangga di Kelurahan Mlatibaru Semarang - Tri Widiastuti; Anandha Anandha; Rahmatya Widyaswati (Journal of Dedicators Community, 2018)
Community empowerment is done to improve people's welfare. Through training activities to make a healthy snack sticks made from raw fish, is expected to explore the potential of people who have high selling value. Development of training conducted in Mlatibaru Semarang village residents so that citizens have a wide repertoire of products related to healthy snacks made from raw fish and simple bookkeeping of the undertakings to be more organized in managing their business finances. Community devotion aims to empower the community to develop expertise in entrepreneurship independently so that it can help improve the quality of life of Mlatibaru Semarang village residents. The result of the devotion is known that the mothers of the citizens of Mlatibaru Semarang village are very motivated to entrepreneurship, by making a healthy snack sticks made from raw fish so that it can supplement family income and can make financial administration in orderly and orderly by making financial bookkeeping.